2011
DOI: 10.1002/smll.201101362
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Obstacles for Bacterial Surface Motility

Abstract: Twitching motility enables bacteria to move over surfaces using type IV pili as grappling hooks. Here it is shown that the motility of the round Neisseria gonorrhoeae as well as of rod-shaped Myxococcus xanthus is guided by elevations with dimension and depth corresponding to the size of the bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 22 publications
8
34
0
Order By: Relevance
“…This phenomenon occurs under stress conditions such as nutrient shortage, oxidative damage, or DNA damage. 32 Therefore, the elongation of E. coli on the pillared films indicates that the nanopillars are inducing stress, corroborating our finding that the surface is bactericidal, and perhaps indicating a secondary mechanism.…”
Section: B Nanotopographical Effects On Cell Morphologysupporting
confidence: 86%
“…This phenomenon occurs under stress conditions such as nutrient shortage, oxidative damage, or DNA damage. 32 Therefore, the elongation of E. coli on the pillared films indicates that the nanopillars are inducing stress, corroborating our finding that the surface is bactericidal, and perhaps indicating a secondary mechanism.…”
Section: B Nanotopographical Effects On Cell Morphologysupporting
confidence: 86%
“…Individual cell motility is rarely observed during twitching motility-mediated interstitial biofilm expansion of P. aeruginosa (Semmler et al, 1999). The observation that individual P. aeruginosa cells preferentially migrate along the furrow edge is reminiscent of the behavior previously reported for Neisseria gonorrhoeae diplococci which were observed to migrate via twitching motility along the edges of the channels etched in PDMS surfaces (Meel et al, 2012). It was proposed that the channel walls provided additional surfaces for the type IV pili of the N. gonorrhoeae to bind to facilitate twitching motility (Meel et al, 2012).…”
Section: Resultssupporting
confidence: 65%
“…These observations suggested that the coordination of multiple pilus motors may be mediated mechanically via a tug-of-war of pilus motors pulling in different directions 15 . Furthermore, diplococci (pairs of bacteria) were observed to align and meander in micro-topographic grooves, consistent with a tug-of-war between pili on either side of the bacterium 33 . Moreover, type IV pili fulfil several prerequisites of a tug-of-war mechanism: the persistence time of the motion increases with the number of pili present on the cell surface and the average unbinding force is by an order of magnitude lower than the maximum force that one pilus can generate 15 .…”
mentioning
confidence: 58%